Artificial Intelligence in Islamic Education: Student Strategies and Challenges in Pedagogical Development - Nasikhin, Nasikhin; Syukur, Fatah; Junaedi, Mahfud; Ridwan, Mohammad; Hasan, Zainudin (Program Pascasarjana, Universitas Islam Bunga Bangsa Cirebon, 2025)
Artificial Intelligence is developing rapidly and is beginning to be widely adopted in higher education, including as a learning tool. However, the integration of AI into the realm of Islamic religious studies raises a number of issues for students, particularly regarding the validity and contextualization of AI responses to religious material rich in historical, linguistic, and spiritual meaning. This study aims to understand how students in the Bachelor of Islamic Religious Education program utilize AI as a tool to improve their pedagogical competence, as well as to identify their perspectives, support systems, and the obstacles they face in this process. Using a qualitative approach with a case study design, data were collected through in-depth interviews, participant observation, and document analysis. The results show that students actively use natural language processing-based platforms—AI technology that enables computers to understand, interpret, and respond to human language, both written and spoken. They also utilize global online learning platforms to broaden their horizons and collaboratively for academic discussions. However, doubts about the AI's responses arise due to its limitations in understanding the cultural, historical, and linguistic context of Arabic, particularly in Qur'anic interpretation and Islamic jurisprudence. To verify this, students compare the AI's results with classical literature, academic references, and direct consultations with experts. Key challenges identified include the gap between Islamic spiritual values ​​and the formal logic of AI, limited digital access in remote areas, low digital literacy, and concerns that reliance on AI could diminish students' critical thinking skills regarding religious texts. These findings provide important contributions to the development of more inclusive and effective learning strategies, considering the thoughtful and contextual integration of AI into religious education in the digital age.